THE EFFECT OF IMMERSION OF MANGROVE Avicennia alba (Tomlinson, 1986) LEAF EXTRACT WITH DIFFERENT CONCENTRATIONS IN PREVENTING BACTERIAL DISEASE Vibrio harveyi (Johnson & Shunk, 1936) IN VANAME SHRIMP (Litopenaeus vannamei) (Boone, 1931) - Farida, Eka Nur; Diantari, Rara; Harpeni, Esti; Wardiyanto, Wardiyanto; Hasani, Qadar; Yulianto, Herman; Yusuf, Maulid Wahid; Susanti, Oktora (University of Lampung, 2020)
Vibriosis is a disease that often attack shrimp culture, some of the most dangerous types of Vibrio bacteria are V. harveyi. The use of natural materials is an alternative that can be applied to prevent bacterial disease. One of the mangrove species that has an antibacterial compound is A. alba. A. alba has alkaloid, saponins, and flavonoids compounds that can inhibit the function of cytoplasmic membranes and energy metabolism in bacteria. This study was conducted to determine the effectiveness of A. alba leaf extract A. alba in inhibiting V. harveyi disease in vaname shrimp (Litopenaeus vannamei). This research was conducted in several stages, namely extraction of mangrove leaves, both in vivo and in vitro. The highest SR, RPS and MTD values were obtamed at a concentration of 250 mg/l with each value of 80 %, 60 %, 75th respectively hour. Mangrove leaf extract A. alba was able to prevent diseases caused by the bacteria V. harveyi, with the best results at an extract concentration of 250 mg/l where the concentration can significantly higher SR, RPS, and MTD compared to other treatments.